PENTINGNYA SARANA PENDIDIKAN DALAM MENUNJANG KUALITAS PENDIDIKAN DI SEKOLAH - Ni Wayan Sri Yustikia (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2017)
Indonesian constitution mandate regarding the effort to improve the nation’s education level is not an easy thing to do and not to be regarded merely as a political product. The mandate is a prerequisite of the glory of The Indonesian republic, and therefore no bargaining should be made over it. The National education Act as the implementation of the mandate in the Indonesian Constitution, has already followed by the increase in the National Education Budget into 20% of the National Income and Expense Budget. Such a fantastic move and this writing will elaborate the use of such fund in real life to accommodate the needs of the students.The vital means of education, starting from the classroom, teaching and learning aids, learning medias, books, journal, and encyclopedia as the source of learning should be improved. Therefore the implementation of the constitution should be based on the empirical needs of education. Brilliant students, the improvement education of Indonesia should be the goal of a great nation such as Indonesia.Key words : Education means, quality, school